2001
DOI: 10.1556/aagr.49.2001.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Manure and Slow-Release N-Fertilizers on the Productivity of Wheat (Triticum Aestivum L.) in Sandy Soil

Abstract: Two field experiments were conducted during the two winter seasons of 1998/1999 and 1999/2000 in a private farm at El-Nagah Village, South El-Tahrir province, El-Behaira Governorate, Egypt. The aim of this study was to compare the effect of different forms of nitrogen fertilizer, i.e., ammonium sulphate 20.6% N, ammonium nitrate 33.5% N, and Enciabien 40% N (slow-release) with or without organic manure at 20 m3/fed (4200 m2) on the yield and nutrient contents of the wheat (Triticum aestivum L.) cultivar Sakha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 4 publications
3
14
0
Order By: Relevance
“…The positive effect of soil K-sulphate application, can be explained by its affect on grains and stover yields, since nutrient uptake calculated by multiplying grain or stover yields by its nutrient percentage (Table 1 and 2 in appendix). Similar results were obtained by Zorkany (2000) and Zeidan and Kramany (2001). .11 32.82 35.22 35.74 36.45 36.74 34.59 35.10 7.17 7.35 8.42 8.10 8.33 8.47 7.97 7.97 20.12 20.71 22.74 22.90 24.23 24.36 22.36 22.65 Considering foliar spraying of potassium, the data indicate that foliar spraying of potassium had a markedly affect on N,P and K uptake.…”
Section: Yieldssupporting
confidence: 91%
“…The positive effect of soil K-sulphate application, can be explained by its affect on grains and stover yields, since nutrient uptake calculated by multiplying grain or stover yields by its nutrient percentage (Table 1 and 2 in appendix). Similar results were obtained by Zorkany (2000) and Zeidan and Kramany (2001). .11 32.82 35.22 35.74 36.45 36.74 34.59 35.10 7.17 7.35 8.42 8.10 8.33 8.47 7.97 7.97 20.12 20.71 22.74 22.90 24.23 24.36 22.36 22.65 Considering foliar spraying of potassium, the data indicate that foliar spraying of potassium had a markedly affect on N,P and K uptake.…”
Section: Yieldssupporting
confidence: 91%
“…According to ref. 61 , the higher 1000 seeds weight was due to the large accumulation of proteins and other reserved food in the seeds, was attributed to the increase in the availability of nutrients when chemical fertilizers were applied mixed with organic manures.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat yield and its attributes were significantly affected by N fertilizer type, where it had higher values under urea form (Table 4). El-Kramany (2001) indicated that slow release of N fertilizer gave the highest 1000-grain mass and grain yield of wheat per unit area. Furthermore, the long growing season of wheat caused great benefits from urea form than urea in the winter season.…”
Section: N Fertilizer Typementioning
confidence: 99%